Investigating the contextual factors and mechanisms associated with implementing Blue Prescription Programmes in health and social care settings: a systematic review using realist synthesis. (October 2022) - Alejandre, Julius Cesar; Chastin, Sebastien; Irvine, Katherine N; Georgiou, Michail; Khanna, Preeti; Tieges, Zoë; Smith, Niamh; Chong, Yong-Yee; Onagan, Frances Claire; Price, Lesley; Pfleger, Sharon; Helliwell, Rachel; et al.
Abstract: Background: Nature-based social prescribing programmes, such as Blue Prescription Programmes (BPPs), promote public health and the health improvement of individuals with long-term conditions. However, there is little evidence that explains the context and mechanisms of implementing BPPs in health and social care settings that could inform policy and practice. Methods: We conducted a systematic realist review by searching six databases (PubMed, Web of Science, PsycInfo, MEDLINE, Scopus, and CINAHL) for articles published in English, between January 2000, and June 2022. We used search terms related to health and social care professionals providing referral to or the prescription of blue space activities with health-related outcomes (eg, [prescription] AND [blue spaces OR river] AND [swimming OR fishing] AND [mental health OR physical health]). We thematically developed contextual factors by analysing the context of implementing BPPs. We used these contextual factors to develop programme theories describing the mechanisms of BPP implementation. Findings: 16 studies with adequate to high quality were included from 8619 records. Service users had improvements to their physical, mental, and social health, as well as their environmental knowledge, after participating in BPPs referred to or prescribed by health and social care professionals. Patient-related contextual factors were referral information, free equipment and transportation, social support, blue space environments, and the skills of service providers. Programme-related contextual factors were communication, multi-stakeholder collaboration, financing, and adequate service providers. Interpretation: Programme theories on patient enrolment, engagement, adherence, communication protocols, and long-term programme sustainability described the mechanisms of BPP implementation. BPPs could support health and social care services if contextual factors, mechanisms, and programme theories associated with patients' characteristics and programme delivery are considered in the planning, development, implementation, and evaluation of similar nature-based social prescribing programmes in health and social care settings. Funding: Scottish Government Hydro Nation Scholars Programme.